2007
DOI: 10.1211/jpp.59.9.0015
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effect of Liuwei Dihuang decoction on early diabetic nephropathy induced by streptozotocin via modulating ET-ROS axis and matrix metalloproteinase activity in rats RETRACTED ARTICLE

Abstract: We aimed to investigate the effects of Liuwei Dihuang decoction (LW) on the endothelin-1-reactive oxidative species (ET-ROS) system and matrix metalloproteinases (MMPs) in the early diabetic nephropathy induced by streptozotocin (STZ) in rats. Rats were divided into six groups as follows: the control group, the untreated model group, the treated groups with the LW (5, 10 and 15 g kg(-1), p.o.) and the aminoguanidine-treated group (100 mg kg(-1), orally). The treatment was performed for 4 weeks, beginning on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…), Corni fructus and Dioscorea opposite (Thunb.). This prescription is used and modified to contain more plant medicines in treating diabetes in China and Japan (Kitagawa et al, 1971;Kiho et al, 1992;Zhang et al, 1996;Yang et al, 2002;Yokozawa et al, 2004;He et al, 2007). Corni fructus is the most attractive and considered as effective fraction for isolating and testing its in relieving DN (Yamabe et al, 2007a(Yamabe et al, , 2007b.…”
Section: Introductionmentioning
confidence: 99%
“…), Corni fructus and Dioscorea opposite (Thunb.). This prescription is used and modified to contain more plant medicines in treating diabetes in China and Japan (Kitagawa et al, 1971;Kiho et al, 1992;Zhang et al, 1996;Yang et al, 2002;Yokozawa et al, 2004;He et al, 2007). Corni fructus is the most attractive and considered as effective fraction for isolating and testing its in relieving DN (Yamabe et al, 2007a(Yamabe et al, , 2007b.…”
Section: Introductionmentioning
confidence: 99%
“…However, only the effective mechanisms of Six-Ingredient Rehmannia Pill and Supplemented Kidney Qi Pill on diabetic nephropathy were explored in molecular biological level. Studies showed that both of the two formulas could reduce renal oxidative injury [9] and decrease expression of serum transforming growth factor~I(TGF-~I) [10], the mainly start factor of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, animal experiments revealed its protective effect on renal injuries of diabetic nephropathy (DN) animal models (Yokozawa et al, 2004;Liu et al, 2008). Clinical studies also reported that ZDP exhibited potentials in the treatment of DN patients (Song et al, 2004;He et al, 2007). However, as TCM usually operates in vivo by multi-components, multiways and multi-targets (Xie et al, 2009), its molecular mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%